Columbus and the ends of the earth : Europe's prophetic rhetoric as conquering ideology - Kadir, Djelal (University of California Press, 1992)
Columbus is the first blazing star in a constellation of explorers whose right to claim and conquer each new land mass they encountered was absolutely unquestioned by their countrymen. Columbus and the Ends of the Earth brings to life the system of religious beliefs that made the imperial taking of the New World not only possible but laudable. The language of prophecy and divine predestination fills the pronouncements of those who ventured across the Atlantic. With their conviction that they were exercising a God-given right to lands and goods held in escrow until the dawning of the Age of Discovery, Spanish, English, and other European adventurers laid claim to the land and peoples of the New World as their rightful due and manifest destiny. Djelal Kadir's argument has profound implications for current theoretical debates and reassessments of colonialism and decolonization. Has the ideology of empire disappeared, or has it merely been secularized? Kadir suggests that in this supposedly postcolonial era, richer nations and privileged multinational entities still manipulate the rhetoric of conquest to justify and serve their own worldly ends. For colonized peoples who live today at the "ends of the earth," the age of exploitation may not be essentially different from the age of exploration. Here is a timely review of the founding doctrines of empire, one that speaks less than reverentially of the brave explorers and righteous settlers of the New World